Pretreatment and Bioconversion of Crop Residues - Martín, Carlos (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this book, 15 papers, covering some of the latest advances in pretreatment and bioconversion of crop residues, are presented. Research results dealing with wheat straw, corn stover, sweet sorghum bagasse, hazelnut shells, oil palm empty fruit bunch, olive tree pruning biomass, and other residues of crop harvest and processing are discussed. Pretreatment methods, such as auto-catalyzed and acid-catalyzed hydrothermal processing, steaming, alkaline methods, and different organosolv approaches, are reported. Bioconversion with enzymes and microbes for producing fermentable sugars, xylitol, and biomethane are also included.